Ukraine war refugees - threats and new challenges for healthcare in Poland. (July 2022) - Lewtak, K.; Kanecki, K.; Tyszko, P.; Goryński, P.; Bogdan, M.; Nitsch-Osuch, A.
Summary: Background: Between February 2022, when the war in Ukraine began, and April 1, 2022, the number of refugees to neighboring countries reached 4, 137, 842 people. The majority have fled to Poland. The main challenge for the health system in Poland in this situation is how to develop effective adaptation measures. Aim: The aim of this study is to describe threats and challenges to public health related in particular to infectious diseases and to identify the resources of the healthcare system that are necessary to meet the needs of the recent war refugees and the Polish population. Methods: Scientific publications, statistical data from national and international organizations, information obtained from public institutions in Poland and Ukraine, and reliable sources of up-to-date information on the Internet were used. Key data on threats and challenges to public health were collected and presented. Findings: Differences were observed between Poland and Ukraine in terms of immunization programmes and their implementation as well as in relation to the prevalence of selected infectious diseases. The increase in demand for healthcare resources in Poland was estimated on the basis of current indicators. Both the possibilities of counteracting epidemic threats related to the current situation and possible consequences for the availability of services and the health condition of all people currently staying in Poland were presented. Conclusion: European countries may experience public health threats due to the influx of war refugees. The data presented could be useful for European countries while developing effective strategies to mitigate public health issues.